WOMEN SPEECH IN ANGRY CONDITIONS IN 7 HATI 7 CINTA 7 WANITA FILM (JENIS-JENIS TINDAK TUTUR PEREMPUAN DALAM KONDISI MARAH PADA FILM 7 HATI 7 CINTA 7 WANITA) - Sabrian, Rahmadani; Sastra, Gusdi; Revita, Ike (Jurnal Gramatika, 2019)
Anger is one of the basic emotion created by every human being. Anger gets into the realm of pragmatic study because this emotion is a verbal act and is a type of illocutionary speech act, especially expressive speech acts. Angry speech is used more by women than by men. This is due to genetic factors in which women are more sensitive and more able to express their anger through speech. This study aims to describe the forms of speech acts used by women in angry conditions. While the subjects in this study are speeches which are indicated as angry speeches on 7 Hati 7 Cinta 7 Wanita films. The research method used is padan method with data collection using simak method and followed by catat technique. The results are as follows (a) direct literal speech act, (b) direct nonliteral speech act, (c) indirect literal speech act, (d) indirect nonliteral speech act.